169k views
0 votes
What is the step by step to get this answer I got

What is the step by step to get this answer I got-example-1

1 Answer

2 votes

Answer:

x = -4, -2

Explanation:

Given equation is,

x² + 6x + 8 = 0

Let the equation to be graphed is,

y = x² + 6x + 8

y = x² + 2(3x) + 9 - 1

y = x² + 2(3x) + 3² - 1

y = (x + 3)² - 1

Table for the Input-output values

x -6 -4 -3 -2 -1 0

y 8 0 -1 0 3 8

Now we can plot these points on the graph as attached.

Since, this graph is intersecting x-axis at x = -4, -2

Therefore, solutions of the given equation will be x = -4, -2

What is the step by step to get this answer I got-example-1
User Ivan Denysov
by
4.9k points